Penguatan kajian keagamaan melalui kajian kitab Fikih Mabadi’: pendampingan keagamaan bagi jemaah musala Al-Hikmah Desa Serut Kecamatan Boyolangu Tulungagung - Chusnul Chotimah; Miftahuddin (PERDIKAN (Journal of Community Engagement), 2023)
Apart from being a large religious and social capital, diverse community backgrounds, heterogeneous social and economic status, occupational professions, different levels of religious understanding, multicultural traditions, and culture are also prone to triggering conflict. Therefore, this needs to be fostered and strengthened by instilling the values of moderation in religious activities in a society that is full of tolerance, nationalism, and acceptance of local traditions and culture. Such an effort was made by the people of Serut Village through the pioneering study of the Islamic classic book, Mabadi Fiqh. With the participation research method beginning with the ideas and initiation of several religious figures and the support of the congregation in the midst of the COVID-19 pandemic, this idea continued into action and has been running consistently since March 2022. The results of a routine yellow book study are as follows: 1) ongoing development of religious awareness of the Al-Hikmah musala congregation; 2) obtaining religious understanding and religious awareness based on religious moderation as religious reinforcement; and 3) an increasingly strong atmosphere of religious life that is peaceful, tolerant, and adapted to local culture and traditions actualized in musala jama'ah Al-Hikmah and the surrounding community. (Latar belakang masyarakat yang beragam, status sosial, ekonomi, dan juga profesi pekerjaan yang heterogen, tingkat pemahaman keagamaan berbeda, tradisi dan budaya yang multikultur, selain menjadi modal sosial agama yang besar, juga rentan memicu timbulnya konflik. Oleh karena itu, hal tersebut perlu dipupuk dan dikuatkan dengan penanaman nilai-nilai moderasi dalam kegiatan-kegiatan keagamaan di masyarakat yang sarat akan nilai toleransi, wawasan kebangsaan, penerimaan terhadap tradisi dan budaya lokal. Upaya demikian dilakukan masyarakat Desa Serut melalui rintisan kajian kitab kuning Mabadi Fikih. Dengan metode participation research diawali dengan ide dan inisiasi beberapa tokoh agama serta dukungan jemaah, di tengah masa Pandemi Covid-19, gagasan ini berlanjut hingga ke aksi dan sudah berjalan secara istiqomah sejak bulan Maret 2022. Hasil dari kajian kitab kuning secara rutin adalah sebagai berikut: 1) berlangsungnya pembangunan kesadaran keberagamaan jemaah musala Al-Hikmah, 2) didapatkannya pemahaman keagamaan dan kesadaran keagamaan berbasis moderasi beragama sebagai penguatan keagamaan, dan 3) semakin kukuhnya suasana kehidupan beragama yang damai, toleran, dan adapted dengan budaya dan tradisi lokal teraktualisasi pada musala jama’ah Al-Hikmah dan masyarakat sekitar.)